Documenting reforms: case studies from India - Narayan, S. (Delhi, 2006)
Documenting Reforms is an attempt at documenting and understanding the process of reforms in India. In eleven of the most important areas, top experts have made an effort to describe the successes and failures that India has experienced in reforms. Many books and papers have been written discussing policy alternatives and strategies for India, mostly involving a critique of the present situation, and a forward-looking evaluation of the available alternatives. This volume is an attempt at a more detailed narrative about what was done and why. The case studies look back; document what was attempted, what worked and what did not work, and the reasons underlying success or failure.
Keywords: Macroeconomic policy reforms